2019
DOI: 10.1136/bmjdrc-2019-000718
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-oxide and incident atherosclerotic events in high-risk individuals with diabetes: an ACCORD trial post hoc analysis

Abstract: IntroductionType 2 diabetes mellitus (T2D) confers high atherosclerotic cardiovascular disease (ASCVD) risk. The metabolite trimethylamine N-oxide (TMAO) derived via gut flora has been linked to excess ASCVD.Research design and methodsWe analyzed data, biospecimens, and major adverse cardiovascular events (MACEs) from the prospective multicenter randomized Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial to assess its value in 330 high-risk individuals with T2D without evident atherosclerotic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…Consistent with our study, a recent paper also failed to show an association between TMAO and CVD in T2D [ 34 ]. This study by Cardona et al .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our study, a recent paper also failed to show an association between TMAO and CVD in T2D [ 34 ]. This study by Cardona et al .…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, another study (10) included two independent large cohort, the Cleveland Cohort and the Swiss Cohort, and results showed that patients in the third quartile of TMAO level in the former cohort but not those in the latter cohort presented significant higher cardiovascular risks, which might be due to a higher TMAO level in the former cohort than in the latter one (the third quartile in the former cohort: 4.28-7.89 uM; the third quartile in the latter cohort: 2.87-4.84 uM). Although previous studies reported TMAO as a prognostic biomarker in patients with heart failure, only a few studies (15)(16)(17)38) evaluated TMAO in patients without established heart failure and surprisingly, these studies all reported non-significant prognostic value of TMAO for cardiovascular outcomes after adjustments for traditional parameters. To our knowledge, our study is the first to investigate the role of TMAO in LVSD after a first anterior STEMI and we did not observe a significant relationship between the two.…”
Section: Discussionmentioning
confidence: 97%
“…TMAO is a metabolite derived from gut flora ( 5 ) and is related to cardiovascular diseases ( 6 11 , 14 ). However, its prognostic utility remains controversial, due to different follow-up intervals ( 11 ), study populations ( 16 , 17 , 38 ), geographical regions ( 10 , 39 ), and ethnicities ( 40 , 41 ). In addition, it has been reported that the core intestinal microbiota in patients with heart failure were usually altered ( 42 ), resulting in significantly increased circulating TMAO levels ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be synthesized from choline, which plays a critical role in lipid metabolism. Not only that, evidences from intestinal microbiology demonstrated that betaine is an important precursor of trimethylamine N-oxide (TMAO), a gut microbiota-dependent metabolite which is indicated as an independent prognostic risk factor for cardiovascular disease and metabolic syndrome [21][22][23].…”
Section: Discussionmentioning
confidence: 99%